Terapi Okupasi (Occupational Theraphy) untuk Anak Berkebutuhan Khusus (Down Syndrome) (Studi Kasus Pada Anak Usia 5 â 6 Tahun di Balai Pengembangan Pendidikan Khusus Semarang) - Irawan, Ria Dewi (BELIA: Early Childhood Education Papers, 2016)
Child with down syndrome have one of them character is muscle weak, short fingers and short feet. Cause of there certainly the children hard to doing activity gross and fine motor skills. One of method therapy is repair occupation therapy. The formulation of the problem in this study (1) how to application therapy occupation to children of special need (down syndrome) on BP-DIKSUS Semarang. (2) What of media and infrastructure to needed when therapy occupation to children special need (down syndrome). (3) How are form evaluation therapy occupation to children special need (down syndrome). Purpose of research is knowing application therapy occupation. Media and infrastructure needed and form of evaluation therapy occupation to children down syndrome Balai Pengembangan Pendidikan Khusus Semarang. This type research used in this study is a qualitative case studies that form the research procedure that produce descriptive data in the form of words, written or spoken words of people, people and observed behavior. The process accumulation data by means of observation, interview, notation, and documentation. Based on this research study indicate therapy occupation that on Balai Pengembangan Pendidikan Khusus Semarang is therapy process (opening and pray, colleague activity and kernel activity), the activity adjusted purpose to realized, be reward and punishment, before the child to treated occupation previous child behavior treated, therapy occupation more given to pre academy, pre motor skill and independence self. Media and infrastructure presence CCTV, tools of gross motor skill is sensory integrity that is (a pool ball, slide, stairs), tools of gross motor skill (puzzle, tassel, sewing tools, color cube), the facility of children got (book related, report, absent card), spot of therapy not appropriation yet. Though form of evaluation on Balai Pengembangan Pendidikan Khusus Semarang is ordinary evaluation. The problem is therapy schedule once in one week, a form of evaluation like a report and book related, and home program. Based of conclusion suggested (1) therapy to raising application and evaluation appropriate of basic and to adding supported therapy media. (2) parent more consistent to send the children and get insight about therapy occupation.